Rationales and instruments for public innovation policies - Tuomas Takalo (Bank of Finland, 2013)
Economic interest in innovation policy largely arises from the fundamental importance of innovation to social welfare and from inefficiencies in innovation in a competitive market environment. As a result, a wide variety of public innovation policies are used in practice. This study reviews the economic justifications for public innovation policies and compares the existing policy tools, paying particular attention to the Finnish innovation policy environment.
URN:NBN:fi:bof-20140807553
Keywords: O38; O34; O31; G28; H25; 330; Innovation policies; innovation; R&D; incentives; market failures